Future projections of river nutrient export to the global coastal ocean show persisting nitrogen and phosphorus distortion - Beusen, Arthur H. W.; Bouwman, Alexander F. (Frontiers in Water, 2022)
Nitrogen (N) and phosphorus (P) from anthropogenic sources are needed to produce food for the growing world population. As a result, these nutrients can be found in nearly every water body across the globe. Not only nutrient loading is important but also the molar ratio and its deviation from the ‘natural’ Redfield ratio. Here we show that rivers, which have more than 50% anthropogenic sources and at the same time elevated N:P ratios (> 25) contributed 36% to the total global N export to coastal waters in 2015. The five Shared Socioeconomic Pathways (SSP) were used in combination with the Representative Concentration Pathways climate scenarios to project river nutrient loadings for 2050. Future nutrient export is projected to decline in high-income countries (with N:P ratios exceeding Redfield). In Brazil, India and China, however, a decline of N:P is only the case in a scenario oriented towards sustainable development (SSP1). The human-dominated river N and P export with elevated N:P ratios will increase in all SSPs, except in SSP1 where it stabilizes. Integrated strategies for both N and P considering all relevant trade-offs and societal sectors are urgently needed to reduce the nutrient pressure on surface waters.